กลวิธีการสร้างกะโหลกซอสามสาย - อรุณรัตน์, อุดม (Journal of the Faculty of Arts, Silpakorn University, 2021)
'Three-string spike fiddle' may be regarded as a truly Siamese spike fiddle played by the Thai from the ancicnt days. It is a bow-type musical instrument of highly valuable craftmanship. Beautifully shaped and resonanced, it can be finely tned tobe weI sychronised with lead-sigWith striking resemblance to human sounds, its sound quality is genuinely unparallelled.